أثر تقلبات عائد الأسهم على حجم التداول في الأسواق المالية "دراسة تطبيقية في سوق دمشق المالي" - المشعل, ياسر; بقلة, سهير; الدكي, رنيم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
سعت هذه الدراسة إلى معرفة ما إذا كان هنالك أية علاقة مهمة بين حجم تداول أسهم الشركات السورية المدرجة في سوق دمشق للأوراق المالية وبين تقلبات عوائد الأسهم الشهرية في تلك السوق، خلال الفترة 1-1-2010 ولغاية 31-8-2014، وإلى معرفة نوع تلك العلاقة (طردية أم عكسية)، لإعطائها الوزن الملائم لها عند محاولة تفسير تقلبات حجم تداول الأسهم في سوق دمشق للأوراق المالية، أو عند التنبؤ بها. ولدى استخدام أسلوب تحليل الانحدار غير الخطي GARCH(1,1)، لمعالجة البيانات المتعلقة بعائد الأسهم في سوق دمشق للأوراق المالية، تبين أن العلاقة بين حجم تداول الأسهم وتقلبات عوائد الأسهم غير مهمة إحصائياً، ولهذا فلا مبرر لأخذ مخاطر تقلبات عوائد الأسهم بعين الاعتبار كعامل مهم عند محاولة تفسير أسباب تقلبات حجم التداول للسوق أو عند التنبؤ بها.This study sought to find out whether there is any significant relationship between the in trading volume shares of Syrian companies listed in the Damascus market Securities Exchange, and Volatility of stock returns monthly in that market, during the period 1-1-2010 till 31-8-2014, and to discover what kind of that relationship (positive or negative correlation) in order to give appropriate weight to them for interpreting fluctuations in the volume of trading in the stock Damascus market Securities Exchange, or for predicting. When using the method of Nonlinear regression analysis method GARCH(1,1) to process the data related to Return on the stock in DSE we found that the relationship between the trading volume shares and volatility of stock returns wasn't statistically significant. This volatility in stock returns mustn't be taken into account as an important factor when trying to explain the reasons for fluctuations in trading volume market or when predicting.